THE EFFECT OF SALES GROWTH, LIQUIDITY AND ASSET STRUCTURE ON PT MUSTIKA RATU'S DEBT POLICY FOR THE PERIOD 2014-2023 - Ida Yusnita; Tiara Lilis Surya; Iin Syofia Yandra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This aim of the research is to examine the effect of sales growth, Liquidity, Structur, Asset Management on debt policy at PT Mustika Ratu Tbk from 2014 to 2023. The research method uses a multiple linear regression method. Simultaneously Sales Growth, Liquidity (Current Ratio) and Asset Structure have a significant influence on Debt Policy as evidenced by F_(count ) > F_tabel (42,044 < 2.76). The magnitude of the influence of Sales Growth, Liquidity (Current Ratio) and Asset Structure on PT Mustika Ratu's Debt Policy for 2014-2023 is 60.6% while the remaining 39.4% is explained by other causal factors not examined in this research